Impaired Cognitive Flexibility After Neonatal Perirhinal Lesions in Rhesus Macaques - Weiss, Alison R.; White, Jessica; Richardson, Rebecca; Bachevalier, Jocelyne (Frontiers in Systems Neuroscience, 2019)
Previous research indicated that monkeys with neonatal perirhinal lesions (Neo-PRh) were impaired on working memory (WM) tasks that generated proactive interference, but performed normally on working memory tasks devoid of interference (Weiss, Nadji, & Bachevalier, 2016). This finding suggested that the early lesions disrupted cognitive processes important for resolving proactive interference such as behavioral inhibition and cognitive flexibility. To distinguish between these possibilities, the same Neo-PRh monkeys and their controls were tested using the Intradimensional/Extradimensional attentional set-shifting task (Dias et al., 1997; Roberts et al., 1988). Neo-PRh monkeys completed the Simple and Compound Discrimination stages, the Intradimensional Shift stage, and all Reversal stages comparably to controls, but made significantly more errors on the Extradimensional Shift stage of the task. These data indicate that impaired cognitive flexibility was the likely source of increased perseverative errors made by Neo-PRh monkeys when performing WM tasks, rather than impaired behavioral inhibition, and imply that the perirhinal cortex and its interactions with the PFC may play a unique and critical role in the development of attentional set shifting abilities.